1989
DOI: 10.1029/jd094id05p06297
|View full text |Cite
|
Sign up to set email alerts
|

Electric field measurements within a severe thunderstorm anvil

Abstract: The anvil cloud of a supercell severe storm in central Oklahoma was penetrated by two free balloons carrying corona probes to measure electric fields. The two balloons passed through the portion of the anvil upstream of the precipitation core and provided information on the charge concentrations and vertical thicknesses of the electric charge regions within the cloud. The trajectories of the balloons relative to the storm were horizontally separated by approximately 35 km, providing information on the horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…At the same time, experimental observations indicate the presence of extended charged regions in the TC structure and the presence of strong electromagnetic regions in the TC and tornado regions (Black and Hallet, 1999;Vonnegut, 1960;Ziegler and MacGorman, 1994;Winn et al, 2000;Krasilnikov 1997;Chalmers, 1967;Williams, 1989;Marshall and Rust, 1995;Byrne et al, 1989). In all similar phenomena one can see the generation mechanism of charged particles by friction (one of the possible mechanisms).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…At the same time, experimental observations indicate the presence of extended charged regions in the TC structure and the presence of strong electromagnetic regions in the TC and tornado regions (Black and Hallet, 1999;Vonnegut, 1960;Ziegler and MacGorman, 1994;Winn et al, 2000;Krasilnikov 1997;Chalmers, 1967;Williams, 1989;Marshall and Rust, 1995;Byrne et al, 1989). In all similar phenomena one can see the generation mechanism of charged particles by friction (one of the possible mechanisms).…”
Section: Introductionmentioning
confidence: 77%
“…The multilayer electrical structures of a cloud cover are observed within thunderstorms (Marshall and Rust, 1995;Byrne et al, 1989). Thus, in the Wayene experiment the electrical structure of 8 charge layers was recorded, the layers being located bottom up (up to 14 km) in the following order: + − + − + − +−.…”
Section: Electromagnetic Characteristics Of Some Atmospheric Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous studies of the third aspect show that the electric structure of a mature thundercloud ( Fig. 1) is the tripole one (Chalmers, 1967;Williams, 1989;Byrne et al, 1989). At an altitude of about 6 km (according to different authors, the range is from 3 to 8 km; Chalmers, 1967) above the Earth's surface, where the air temperature is about −15 • C, there is the center of the negatively charged layer.…”
Section: Action Of Electric Forces In Cloudsmentioning
confidence: 99%
“…As for the first two aspects, in spite of extensive and prolonged studies [e.g., Workman and ReynoMs, 1950;Vonnegut, 1953;Chalmers, 1967] there is till now no common viewpoint both with respect to the mechanism of electric charge formation during cloud forming and with respect to the process of their separation. However, numerous studies of the third aspect showed that the electric structure of mature powerful thunderstorms is the tripole one [Chalmers, 1967;Williams, 1989;Byrne et al, 1989]. …”
Section: Electromagnetohydrodynamic (Emhd)mentioning
confidence: 99%